On the bounds of multivalently starlikeness and convexity - Shigeyoshi Owa; Mamoru Nunokawa (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to prove some interesting results for the bounds of starlikeness and convexity of certain multivalent functions.